Synergistic and Antagonistic Interactions Between Varroa destructor Mites and Neonicotinoid Insecticides in Male Apis mellifera Honey Bees - Bruckner, Selina; Straub, Lars; Neumann, Peter; Williams, Geoffrey R. (Frontiers in Ecology and Evolution, 2021)
Pressures from multiple, sometimes interacting, stressors have negative consequences to important ecosystem-service providing species like the western honey bee (Apis mellifera) (hereafter honey bee). The introduced parasite Varroa destructor and the neonicotinoid class of insecticides each represent important, nearly ubiquitous biotic and abiotic stressors to honey bees, respectively. Previous research demonstrated that they synergistically interact to negatively affect non-reproductive honey bee females (workers), but no data exist on how concurrent exposure may affect reproductive honey bee males (drones). This is important, given that the health of reproductive females (queens), possibly because of poor mating, is frequently cited as a major driver of honey bee colony loss. To address this, known age cohorts of drones were obtained from 12 honey bee colonies – seven were exposed to field-relevant concentrations of two neonicotinoids (4.5ppb thiamethoxam and 1.5ppb clothianidin) during development via supplementary pollen patties; five colonies received patties not spiked with neonicotinoids. Artificially emerged drones were assessed for natural V. destructor infestation, weighed, and then allocated to the appropriate treatment group: 1. Control, 2. V. destructor only, 3. Neonicotinoid only, and 4. Combined. Adult drones were maintained in laboratory cages alongside attendant workers (1 drone : 2 worker ratio) until they reached sexual maturity at 14 days post-emergence so sperm quality could be assessed. We found that V. destructor and neonicotinoids interacted synergistically to negatively affect adult drone survival, but that they interacted antagonistically on emergence mass. Although sample sizes were too low to assess the effects of V. destructor and combined exposure on sperm quality, we observed no influence of neonicotinoids on sperm quantity or viability. Our findings highlight the diverse effects of concurrent exposure to stressors on honey bees, and suggest that V. destructor and neonicotinoids can severely effect the number of mature adult drones available for mating.